Meaning, Colouring, and Logic: Kaplan vs. Frege on Pejoratives - Soutif, Ludovic (Princípios: Revista de Filosofia (UFRN), 2022)
Although Frege’s aim was not to provide a semantic theory for a natural language, he made, to say the least, valuable and enduring contributions to semantic theory, understood as the assignment of semantic values, and possibly, further meaning properties to natural language expressions. His arguing, notably in Frege (1892), for the assignment to any well-formed linguistic expression of a sense (Sinn), in addition to its reference (Bedeutung) — if any—, is one — and, arguably, the most celebrated and disputed among his contributions.